Spontaneous chylous ascites after laparoscopic cholecystectomy:a case report - Bansal, Arpit; Bansal, Ashwani Kumar; Bansal, Vandana; Singh, Mamta (International Surgery Journal, 2016)
Cholecystitis with cholelithiasis is a very common disease in clinical practice. Now a days it is treated by laparoscopic cholecystectomy very safely with minimal trauma, discomfort and short hospital stay. Rarely, it is complicated by post-operative chyle leakage in peritoneum. We present a case of spontaneous chylous ascitis after laparoscopic cholecystectomy. Probably idiopathic or caused by trauma of pneumoperitoneum, abnormal peritoneal reaction to various chemicals released during operative procedure and diathermy used during laparoscopic cholecystectomy. We discuss its review, clinical presentation, diagnosis, treatment and management of this case. Chyle leake is rare post-operative complication can be managed by simple conservative treatment.